INFLUENCE ON INVESTMENT, GOVERNMENT EXPENDITURE AND THE LABOR FORCE ON ECONOMIC GROWTH IN INDONESIA - Agus Muliadi Bancin; Murtala Murtala (LPPM Universitas Malikussaleh, 2020)
This study aims to determine the effect of investment, government spending, and labor force on economic growth in 34 provinces in Indonesia. This study uses panel data from 2014 to 2018 accessed on www.bps.go.id and www.bkpm.go.id. The method of data analysis used is panel data regression analysis. The results of partially show that investment has not significant effect on economic growth in 34 provinces in Indonesia, government spending has a negative and significant effect on economic growth in 34 provinces in Indonesia, and the labor force has not significant effect on economic growth in 34 provinces in Indonesia. Simultaneously, investment, government spending, and labor force have a positive and significant effect on the economic growth of 34 provinces in Indonesia. Keywords: Investment, Government Expenditure, Labor Force, Economic Growth.